Annotated Checklist of Chinese Cladocera (Crustacea: Branchiopoda). Part I. Haplopoda, Ctenopoda, Onychopoda and Anomopoda (families Daphniidae, Moinidae, Bosminidae, Ilyocryptidae) - Xiang, Xian-Fen; Ji, Gao-Hua; Chen, Shou-Zhong; Yu, Gong-Liang; Xu, Lei; Han, Bo-Ping; Kotov, Alexey A.; Dumont, Henri J. (Zootaxa, 2015)
Approximately 199 cladoceran species, 5 marine and 194 freshwater and continental saltwater species, live in China. Of these, 89 species are discussed in this paper. They belong to the 4 cladoceran orders, 10 families and 23 genera. There are 2 species in Leptodoridae; 6 species in 4 genera and 3 families in order Onychopoda; 18 species in 7 genera and 2 families in order Ctenopoda; and 63 species in 11 genera and 4 families in non-Radopoda Anomopoda. Five species might be endemic of China and three of Asia. Many records are suspect at the species level, and numerous taxonomic problems remain to be settled.